Photoionization of the I 4d and valence orbitals of methyl iodide. (25th June 2020) - Forbes, Ruaridh; De Fanis, Alberto; Rolles, Daniel; Pratt, Stephen T; Powis, Ivan; Besley, Nicholas A; Milosavljević, Aleksandar R; Nicolas, Christophe; Bozek, John D; Holland, David M P
Abstract: The photoabsorption and photoionization dynamics of the I 4d and valence orbitals in methyl iodide have been studied both experimentally and theoretically. Synchrotron radiation has been employed to measure the total ion yield in the vicinity of the I 4d ionization thresholds. The observed structure, due to excitations into Rydberg or valence states, has been assigned using transition energies and relative intensities computed with time-dependent density functional theory within the Tamm–Dancoff approximation. Photoelectron spectra, recorded with plane polarized radiation in two polarization geometries, have allowed the effect of autoionization on the valence electron angular distributions to be investigated. The spectra obtained at photon energies of 50.62 and 52.34 eV, coinciding respectively with the I 4d5/2 → σ * and 4d3/2 → σ * transitions, reveal, in addition to valence shell photoelectron bands, features not associated with simple photoionization of the parent molecule. High resolution photoelectron spectra of the I 4d main-lines display structure resulting from spin–orbit coupling and molecular field splitting. The binding energies of the five states contributing to the (I 4d) −1 ionization have been determined. The iodine (in CH3 I) N45 VV Auger spectrum has been measured and the observed structure has been assigned using the core hole binding energies derived in the present work together with established ionization energies of the doubly charged ion. The experimentally determined Auger electron angular distributions have been discussed in relation to the theoretical angular distribution parameter characterizing the spatial alignment of molecular axes in the (I 4d) −1 state.